Arctic PASSION Sharing Circle ... - Grosfeld, Lisa; Lenz, Josefine (Zenodo, 2024)
Arctic research is moving increasingly towards being application-oriented, based on the needs of the people who directly face the impacts of accelerating change in the Arctic. In fact, grown up in a world of global challenges, Arctic youth and early career professionals have the power to create positive change. The Arctic benefits from a close dialogue between Arctic youth, young professionals and early career researchers working and living in the Arctic. The Arctic PASSION Sharing Circle fostered this dialogue by inviting eighteen international participants from 9 countries to Sevettijärvi and Inari, Northern Finland, from 2-6 October 2023. The participants learned from and discussed with the Arctic PASSION partner Snowchange about the local Skolt Sámi culture, as well as indigenous-led and co-managed environmental restoration projects of the region. Lively discussion rounds to various relevant topics and a lot of exchange among the group were an integral part of the Sharing Circle. Spending every day ...